Isolation and identification of secondary metabolites in ethyl acetate extract from the Maja bark (Aegle marmelos Linn.) - Muhammad Syahrir; Eka Bungin Kadola; Pince Salempa (Pharmaciana, 2021)
This exploratory study resulted in the isolation and identification of secondary metabolites in ethyl acetate extracts from the Maja bark (Aegle marmelos Linn.) from Pattappa Village, Pujananting Subregency, Barru Regency, South Sulawesi. The stages of isolation included maceration, fractionation, and purification. Maceration was performed with methanol, fractionation with ethyl acetate, a particular ratio of acetone (9:1) was used, and purification was done by flowing nitrogen gaseous into the E5 fraction. Furthermore, the classification test and FTIR spectrophotometer were carried out for identification. Pure isolates in the form of white crystals were obtained with a melting point of 242oC. Reagent tests indicated a brown precipitate on Wagner's test and a white precipitate on Mayer's test. Infrared-spectrophotometric identification provided typical absorption for such functional groups as NH, aliphatic CH, aromatic C=C, and amine CN.Â  The reagent tests and FTIR-spectrophotometer identification confirmed that the secondary metabolites fit well into the class of alkaloids.